Safety boot with pressure sensor LED light / Sharmilah Pilson and Azira Ibrahim - Pilson, Sharmilah; Ibrahim, Azira (2023)
In general, the construction industry is a major contributor economic growth and plays a crucial role in shaping a country’s image. Given the industry’s significance, this research focuses on improving the current safety boots, which are crucial safety gear on construction sites. The research problem addressed in this study includes a lack of safety awareness, poor management, and hazardous working environments. The aims of the research are to identify the construction workers who did not wear safety boots on the construction sites. In addition, the methods used to get information are design thinking, document analysis, review of secondary data, and modelling using SketchUp software. Therefore, the finding of this report are creation of the product idea, development of the proposed product, performance evaluation of the product and marketability potential of the product. The creation of safety boots featuring a pressure sensor light-emitting diod (LED ) light offers an advantage to its consumer, especially for construction workers in Malaysia. This product was created as part of this project to ensure that all construction workers are equipping themselves with the supplied boots when working.